Improving The Potential of Tourism Assets Through Souvenirs in Soko Village, Miri District, Sragen Regency - Arif Ranu Wicaksono; Deny Tri Ardianto; Sayid Mataram; Anugrah Irfan Ismail; Rudy Wicaksono Herlambang (Institut Seni Indonesia Denpasar, 2023)
Villages have a variety of potential assets, one of which is the tourism sector. Under the management of Badan Usaha Milik Desa (BUMDes), a centralized and profit-oriented village asset management unit, tourism assets can impact village progress. A medium that can provide information to the public about tourism assets and simultaneously generate profits is needed. Soko Village in Miri District, Sragen Regency, has potential tourism assets managed by BUMDes SOKO WIJAYA. This village uses tourist souvenir t-shirts that can introduce its tourism assets to the public and generate profits from their sales. Training for village youth as human resources is required to produce souvenir t-shirts with trend-setting designs and effective and efficient production. The result of this research and training activity can improve and introduce the village's potential by optimizing tourism assets and human resources.